Effect of composition on tensile properties and fracture toughness of Al–Zn–Mg alloy (A7N01S-T5) used in high speed trains. (5th February 2016) - Qin, C.; Gou, G.Q.; Che, X.L.; Chen, H.; Chen, J.; Li, P.; Gao, W.
Abstract: The Al–Zn–Mg aluminum alloy A7N01S-T5 used in high speed trains was designed by orthogonal method. The effect of elemental composition on the tensile properties and fracture toughness has been investigated. The alloys with different compositions were tested by tensile and three point bending tests: the range analysis results showed that the compositions of Zn and Mg were the main factors that affect the strength and plasticity of the alloys. The tensile testing results showed that the #1 alloy Al-4.34Zn-1.43 Mg-0.27Mn-0.13Cr-0.12Zr-0.07Ti had the best combination of tensile strength, yield strength and elongation, which were 415 MPa, 378 MPa and 13.5%, respectively. Furthermore, this alloy showed the excellent ability to hinder the crack propagation with a value of J0.2BL( 12)  = 23.37 kJ·m − 2 . The microstructure, grain size, compositions and fracture characteristics of the alloy were investigated by optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectrometer (EDS), backscattered electron diffraction (EBSD) and transmission electron microscopy (TEM). The results indicated that the strength is mainly determined by the volume fraction, size and distribution of precipitated η′(MgZn2 ) phase. The discontinuous distribution of η(MgZn2 ) phase, narrow precipitated-free zones (PFZs) and fine grain size played important roles to obtain high fracture toughness. Graphical abstract: Highlights: The Al–Zn–Mg aluminum alloys A7N01S-T5 were designed by orthogonal method. The effects of compositions on the tensile strength and fracture toughness were studied. The compositions of Zn and Mg were the main factors that affect the strength and plasticity of the alloys. The Al-4.34Zn-1.43 Mg-0.27Mn-0.13Cr-0.12Zr-0.07Ti had the best combination of mechanical properties.